Feasibility, Safety, and Patient Satisfaction of Transurethral Bladder Tumor Resection in an Outpatient Setting - Lucas Strahl; Hendrik Borgmann; Julian Peter Struck; Johannes Salem; Timur H. Kuru (Cancer Reports)
ABSTRACT Introduction Transurethral resection of the bladder (TURB) is a common urological procedure, typically performed in an inpatient setting. This study aims to investigate safety, quality, and patient satisfaction aspects of TURB in an outpatient setting, reflecting the emerging strategy of outpatientization of surgical procedures in the German healthcare system. Methods We retrospectively analyzed a cohort of 100 patients who underwent outpatient TURB. The standard procedure was day surgery under general anesthesia and dismissal with or without a urinary catheter. The analysis focused on postoperative complications, resection quality, recurrence within 6 months, and patient satisfaction. Data was collected from electronic medical records and patient interviews and analyzed using descriptive and multivariate statistics. Results The cohort consisted primarily of male patients (79%) with a median age of 70 years. The average surgery time was 11.3 min with a mean of 1.6 tumors resected. Histopathological findings leaned toward superficial bladder tumors with a mean recurrence rate of 11.6%. Postoperative complications were mostly mild, with only 5% of patients suffering from complications rated as Clavien–Dindo ≥ 2 and no complications of grade ≥ 4. High levels of patient satisfaction were reported, with 83% preferring outpatient TURB to inpatient treatment for future surgery. Conclusion Outpatient TURB appears to be a safe and effective alternative to inpatient surgery for selected patients with bladder tumors ≤ 4 cm, offering comparable surgical and oncological outcomes while enhancing patient satisfaction and reducing healthcare system burden.